The role of neutrophils in vasculitis associated with antineutrophil cytoplasmic antibodies - E. N. Vorkel; T. M. Reshetnyak; A. M. Lila (Современная ревматология)
Vasculitis associated with antineutrophil cytoplasmic antibodies (AAV) is a potentially dangerous autoimmune disease characterized by necrotizing inflammation of small blood vessels. In the pathogenesis of AAV, both innate and adaptive immunity are closely linked to neutrophil function. The study of the pathogenetic mechanisms of neutrophil activation in AAV may serve as a prerequisite for the development of more accurate and modern methods of laboratory diagnostics as well as new treatment approaches targeting neutrophils. The review presents an analysis of studies addressing the issue of neutrophil activation in AAV.